Democracy of Inclusion or Exclusion? Understanding and Analysing the Scheduled Castes and the Scheduled Tribes (Prevention of Atrocities) Act, 1989 (Global Journal of Human-Social Science, 2019)
Introduction -T he Indian Constitution upholds the right to social, economic and political justice to all the citizens. Democratic institutions and elected representatives collectively engage in ensuring the exercise of fundamental rights without infringement. However, to say that a democratic society is free of social perils, is preposterous. Among social conflicts, incidents revolving around communal or religious disharmony often result in subjugation and repression. Although law takes its course, the prolonged delay in investigation and justice leads to the perpetuation of heinous atrocities against the socially disadvantaged.